The Value of Technological Approaches in Teacher Education for Integrating Digital Learning Technologies of Teaching Leaning Process - Maiti, Dilip (Journal of Research in Innovative Teaching and Inclusive Learning, 2024)
These days, no teacher preparation course is complete without instruction in technological literacy. Technology is seen as an essential component of teacher education by governments, education systems, researchers, school administrators, instructors, and parents on a global scale. The researchers set out to find out how useful technical methods are for incorporating digital learning tools into teacher preparation programmes. Technology usage and school competency, the teacher-student relationship, the classroom setting and pedagogical methods, and the incorporation of digital learning tools were the four primary areas of discussion. All schools that prepare teachers should include ICT into their pedagogical methods, which is central to the research. The researchers in this study used a mixed-methods strategy. Teachers and students from different schools participated in interviews, questionnaires, and classroom observations to compile the data. Four statistics studies' quantitative data and four case studies' qualitative data were pooled. Data were used in this investigation to supplement one another. The findings show that there have been significant shifts in pedagogical methods at schools that train teachers and have used technology initiatives to improve education. The gender gap in the usage of digital learning tools for instruction is a direct outcome of this. In the classroom, male instructors tend to utilise their superior talents for more technologically focused initiatives, while female teachers and trainee teachers choose to employ more commonplace technology for teaching and learning. The purpose of this research is to provide light on the potential for incorporating technology into the teaching and learning process, which may then be used by administrators, policymakers, and teacher educators as a whole.